2020
DOI: 10.2147/copd.s234882
|View full text |Cite
|
Sign up to set email alerts
|

<p>Arterial Stiffness Increases Over Time in Relation to Lung Diffusion Capacity: A Longitudinal Observation Study in COPD</p>

Abstract: Background: Cardiovascular events are, after cancer, the most common cause of death in COPD patients. Arterial stiffness is an independent predictor of all-cause mortality and cardiovascular events. Several cross-sectional studies have confirmed increased arterial stiffness in patients with COPD. Various mechanisms in the development of arterial stiffness in COPD such as reduced lung function or systemic inflammation have been proposed. However, clinical predictors of arterial stiffness that had been reported … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 39 publications
0
7
0
2
Order By: Relevance
“…The researchers assessed the arterial stiffness of the included patients by annual measurement of the AIx over a period of 7 years and concluded a significant increase in arterial stiffness in their patients' overtime. Moreover, the amount of annual increase in AIx was correlated to the severity of emphysema [12]. On the other hand, pulmonary rehabilitation was found to have a possible role in modification of elevated aortic stiffness in a subgroup of COPD patients [24].…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…The researchers assessed the arterial stiffness of the included patients by annual measurement of the AIx over a period of 7 years and concluded a significant increase in arterial stiffness in their patients' overtime. Moreover, the amount of annual increase in AIx was correlated to the severity of emphysema [12]. On the other hand, pulmonary rehabilitation was found to have a possible role in modification of elevated aortic stiffness in a subgroup of COPD patients [24].…”
Section: Discussionmentioning
confidence: 95%
“…Cardiovascular events were found to be the second most common etiology of mortality following bronchogenic carcinoma in COPD patients [12]. The early affection of the cardiovascular system is important to solve the mystery of such a disease, which is now documented to have a wide range of systemic impact on the whole body.…”
Section: Discussionmentioning
confidence: 99%
“…The association between D LCO measures and arterial stiffness has been investigated in COPD patients [26] where arterial stiffness as indirectly measured by the J o u r n a l P r e -p r o o f augmentation index in COPD patients has been related to the severity of emphysema as measured by D LCO [26]. Additionally, greater arterial stiffness as measured by aortic PWV was found in COPD patients with mild disease and was related to the emphysema burden and low D LCO , regardless of FEV 1 impairment.…”
Section: Discussionmentioning
confidence: 99%
“…Cardiovascular disease is the most common chronic disease associated with COPD, a major cause of hospitalization, and also one of the leading causes of death 4 . Previous studies have shown that patients with COPD are at increased risk of atherosclerosis, and the mechanism may be related to hypoxemia and inflammation [5][6][7] . Arterial stiffness is highly relevant to cardiovascular disease and is an important arterial phenotype and an excellent indicator of cardiovascular morbidity and mortality.…”
Section: Introductionmentioning
confidence: 99%
“…Arterial stiffness is highly relevant to cardiovascular disease and is an important arterial phenotype and an excellent indicator of cardiovascular morbidity and mortality. In clinical practice, measurements of arterial stiffness is currently one of the most commonly used methods to predict cardiovascular risk in patients with COPD 5,7,8 . Of note, early evaluation of arterial stiffness in patients with COPD is of great significance for the treatment and prognosis of the disease.…”
Section: Introductionmentioning
confidence: 99%